The Socio-Cultural Background of the Genesis of the Lublin-Volhynia Culture - Kadrow, Sławomir; Zakościelna , Anna (Analecta Archaeologica Ressoviensia, 2024)
The direct sources for the study of the origin of many constitutive elements of the Lublin-Volhynian culture (hereafter: L-VC) from various and sometimes distant areas of a culturally diverse nature prompt us to outline the cultural situation in the second half of the 5th millennium BC , and especially in the final phase, in the vast areas of Southeastern Europe and adjacent parts of Eastern Europe. The rationale behind such a move is to help understand this culture and its multifaceted origins. Like a “posthumous child”, it appeared at the last moment of the existence of some cultures belonging to the same cultural complex, i.e., the Early Eneolithic Cultural Complex (hereafter: EECC ), at the latest around 4100 BC . Paradoxically, the Cucuteni-Trypillia Cultural Complex (hereafter: CTCC ) in its younger part of the BI phase (4230–4100 BC ; cf. Diachenko et al. 2024), with a socio-cultural profile distant from the EECC , seems to be the leading “source” of the constitutive elements of the new culture, i.e. the L-VC. The CTCC was the only cultural entity that did not disappear during this period but rather expanded rapidly.